2015
DOI: 10.4330/wjc.v7.i6.311
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary experience with drug-coated balloon angioplasty in primary percutaneous coronary intervention

Abstract: We evaluated the clinical feasibility of using drug-coated balloon (DCB) angioplasty in patients undergoing primary percutaneous coronary intervention (PPCI). Between January 2010 to September 2014, 89 ST-elevation myocardial infarction patients (83% male, mean age 59 ± 14 years) with a total of 89 coronary lesions were treated with DCB during PPCI. Clinical outcomes are reported at 30 d follow-up. Left anterior descending artery was the most common target vessel for PCI (37%). Twenty-eight percent of the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…These findings were supported by Ho et al using the SeQuent Please DEB in the treatment of 89 patients presenting with STEMI [73]. Thrombus aspiration was performed in 56% and predilatation in 100% of patients before DEB treatment, which yielded a low 4% bailout rate.…”
Section: Drug-eluting Balloonssupporting
confidence: 57%
“…These findings were supported by Ho et al using the SeQuent Please DEB in the treatment of 89 patients presenting with STEMI [73]. Thrombus aspiration was performed in 56% and predilatation in 100% of patients before DEB treatment, which yielded a low 4% bailout rate.…”
Section: Drug-eluting Balloonssupporting
confidence: 57%
“…Predilatation was done on a 1:1 balloon to artery ratio basis and the decision to treat with DCB was only made after initial predilatation. Our previous published study on DCB angioplasty revealed only 4% of the patients required bailout stenting for significant recoil/dissection (>type B dissection) …”
Section: Discussionmentioning
confidence: 97%
“…5 Drug-coated balloons (DCB) have recently emerged as a potential therapeutic strategy for patients with small vessel de novo coronary artery disease, 6,7 even in the setting of primary angioplasty. 8 DCB allow rapid and uniform tissue delivery of paclitaxel to the lesion of interest and is an established treatment modality for in-stent restenosis. 9 In de novo disease, a DCB strategy allows stent-free revascularization, thereby removing the detrimental effect of metal from the equation that drives LLL.…”
Section: Introductionmentioning
confidence: 99%
“…DCBonly PCI was carried out in 96%, while the other 4% had bail out stenting for significant acute recoil or dissections. They reported a death rate of 4.5%, MI 0%, and TLR/TVR of 0% at 30 days [19].…”
Section: Evidence For Dcb Angioplasty In Ppcimentioning
confidence: 99%